Peningkatan Kemampuan Membaca pada Layanan Remedial untuk Anak Disleksia melalui Penggunaan Permainan Kartu Kata Siswa Kelas III SDN Kelapa Gading Timur 03 Jakarta Utara - Miftahul Zannah (Peneliti.net, 2018)
This study aims to find out how to improve reading skills in Indonesian language through the use of techniques and techniques for third grade students of SDN Inklusi Kelapa Gading Timur 03 North Jakarta. This study also aims to improve the quality and efficiency of learning. The research method in this research is action research which aims to improve the quality and efficiency of learning. In this study clothes to improve the reading ability of dyslexic children in grade III students. Data on student learning outcomes on average average repair service ability for dyslexic children Measurement from cycle I was 61.14% to 81.14% in cycle II. Whereas the average results of student action monitoring amounted to 30.00% from 60.00% to 90.00%, as well as monitoring the attitudes of attribution teachers by 26.66% from 66.67% to 93.33%. Improved reading skills in remedial program services for dyslexic children that show improvement from cycle I to cycle II